2020
DOI: 10.1016/j.chemosphere.2020.126737
|View full text |Cite
|
Sign up to set email alerts
|

A short review of bioaerosol emissions from gas bioreactors: Health threats, influencing factors and control technologies

Abstract: h i g h l i g h t sThe biofiltration generally emit more than 10 4 CFU m À3 bioaerosol. The bioaerosol emitted from the biofiltration is a potential threat to human body. Shear force and dilution affect the concentration of bioaerosol emissions. PCD is promising to control bioaerosols because of few secondary pollutants. a b s t r a c tBioaerosols have widely been a concern due to their potential harm to human health caused by the carrying and spreading of harmful microorganisms. Biofiltration has been general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…Most researchers from countries with temperate or continental climates reported higher fungal aerosols during the warm season compared to the cold season (Cyprowski et al 2019 ; Fernanda et al 2020 ; Fraczek et al 2017 ; Madhwal et al 2020 ). The humid environment supports maximum growth of bacteria, while fungi proliferate quickly in a dry environment (Hu et al 2020 ). High relative humidity facilitates the fungal species to breed and form more compact colonies, leading to the lower release of fungal propagules into the atmosphere (Breza-Boruta 2016 ; Vilavert et al 2012 ).…”
Section: Temporal Variations In Bioaerosol Concentrationsmentioning
confidence: 99%
“…Most researchers from countries with temperate or continental climates reported higher fungal aerosols during the warm season compared to the cold season (Cyprowski et al 2019 ; Fernanda et al 2020 ; Fraczek et al 2017 ; Madhwal et al 2020 ). The humid environment supports maximum growth of bacteria, while fungi proliferate quickly in a dry environment (Hu et al 2020 ). High relative humidity facilitates the fungal species to breed and form more compact colonies, leading to the lower release of fungal propagules into the atmosphere (Breza-Boruta 2016 ; Vilavert et al 2012 ).…”
Section: Temporal Variations In Bioaerosol Concentrationsmentioning
confidence: 99%
“…Several factors involved in the evaporation/distillation of urine can inactivate pathogens. High temperature is highly effective to inactivate pathogens as reported in the fields of waste composting or water disinfection (Chu et al, 2019;Hu et al, 2020). Moreover, Bethune et al (2014) suggested that the urine-derived solid product was sterile because high salinity in the concentrated product might respond for the inactivation of microorganisms.…”
Section: Evaporation/distillationmentioning
confidence: 97%
“…According to China's "Indoor Air Quality Standards" (GB/T 18883-2002), the bioaerosol concentrations of the three sampling sites at each airspeed belonged to the "clean level" (the total bioaerosols <3,000 CFU m −3 , bacteria <1,000 CFU m −3 , fungi <500 CFU m −3 ). Hu et al (2020) showed that the concentration of bioaerosols emitted from bioreactors ranges from 10 3 to 10 6 CFU m −3 . Zhang et al (2017) detected that the average annual bacterial concentration of airborne bioaerosols in the Beijing-Tianjin-Hebei region was 1,380-3020 CFU m −3 and fungi were 89-2270 CFU m −3 .…”
Section: Bioaerosol Emission Concentrationmentioning
confidence: 99%